An analytical assessment of industrial sector innovative management in the context of digitalization - Nurzhanat Sherimova; Baurzhan Isabekov; Miras Alkeev; Zhanna Yermekova; Tatyana Ostryanina (Journal of Innovation and Entrepreneurship, 2022)
The accumulated potential in digitalization suggests the need to create a new paradigm for managing scientific-innovative and production-technological processes, which is reflected in the author's article. In these conditions, there is the problem of developing a mechanism for innovative management of the industrial sector of the economy. The study aims to analyze statistical and analytical data of modern industrial sector management in the context of digitalization. By analytical, comparative, and statistical analysis of international innovation management approaches, according to the rating of the global innovation index 2020/2021 and business activity of technological leaders in Asia, North America, and Europe, the authors developed a methodological approach to improve the mechanism for implementing innovative management in industrial sector. The mechanism includes such core elements: state industrial policy-purposes of industrial development-decision on innovative management implementation-development of mechanism to implement innovative decision-expected short- and long-term results based on the traceability of innovation and the overall economic context from a global perspective. The study results can be applied for implementing innovative management in industrial sector and developing industrial policies.
Keywords: 650; Digitalization; Industry; Innovation management; Management transformation; Technology